2017
DOI: 10.5194/bg-2017-413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering biological soil crusts: Carbon content and structure of intact Arctic, Antarctic and alpine biological soil crusts

Abstract: Abstract. Arctic, Antarctic and alpine biological soil crusts (BSCs) are formed by adhesion of soil particles to exopolysaccharides (EPS), excreted by cyanobacterial and green algal communities, the pioneers and main producers in these habitats. These BSCs provide and influence many ecosystem services such as soil erodibility, soil formation and Nitrogen-(N) as well as carbon-(C) cycles. In cold environments degradation rates are low and BSCs increase continuously soil organic C, whereby these soils are consid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…On the other hand, soil properties such as pH, organic carbon, nitrogen, and phosphorous contents are very similar at Antarctica and the Arctic sites (Mann, Sletten, & Ugolini, ; Otero, Fernández, de Pablo Hernandez, Nizoli, & Quesada, ). Confocal laser scanning microscopy (CLSM) images of the BSCs from Geopol showed that these factors lead to a thin photosynthetic active layer (PAL; Jung et al., ). Differences between BSC functional group compositions of Geopol and Ny‐Ålesund were shown by Williams, Borchhardt, et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, soil properties such as pH, organic carbon, nitrogen, and phosphorous contents are very similar at Antarctica and the Arctic sites (Mann, Sletten, & Ugolini, ; Otero, Fernández, de Pablo Hernandez, Nizoli, & Quesada, ). Confocal laser scanning microscopy (CLSM) images of the BSCs from Geopol showed that these factors lead to a thin photosynthetic active layer (PAL; Jung et al., ). Differences between BSC functional group compositions of Geopol and Ny‐Ålesund were shown by Williams, Borchhardt, et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hochtor harboring the most diverse cyanobacteria dominated BSC supports previous ideas. An extremely thick PAL structure was visualized by CLSM connected to high diversity for Hochtor and the opposite for Livingston Island (Jung et al., ). Besides water availability the light regime could also be a responsible factor, because all four sites share similar daylight times with photosynthetic active radiation (PAR) exceeding 1200 μmol m −2 s −1 (Barták, Váczi, & Hájek, ; Colesie, Green, Raggio, & Büdel, ; Xiong & Day, ), but with the strongest fluctuations at Hochtor (Büdel et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations